Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If sin theta + cos theta =p and sec thet + cosec theta = q , show that q ( p square - 1) = 2p

If sin theta + cos theta =p and sec thet + cosec theta = q , show that q ( p square - 1) = 2p

Grade:10

2 Answers

SYED FAHIM AHAMAD
20 Points
4 years ago
q(p square -1)=sec theta +cosec theta ( (sin theta +cos theta )square -1)=1/cos theta +1/sin theta (2sin theta cos theta )=(sin theta +cos theta )2=2p
 
Jayanth Miriyala
26 Points
4 years ago
q(p^2-1)= sec theta + cosec theta((sin theta +cos theta)^2 -1)
sec theta + cosec theta( sin^2 theta + cos^2 theta + 2 sin theta cos theta)-1)             (sin^2 theta + cos^2 theta=1)
1/cos theta +1 /sin theta(2 sin theta cos theta)            take LCM
sin theta+ costheta/sin theta cos theta(2 sin theta cos theta)
 
2(sin theta+ cos theta) = 2p

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free